Capital Structure and Dividend Policy - Mei Eka Wardini; Yuli Dwi Yusrani Anugrah; Muhammad Farid; Alfiatul Laili (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam syarifuddin Lumajang, 2022)
The Capital Structure describes the combination of various components on the right side of the balance sheet. In general, it is a combination of debt and equity where the composition of the company's debt and capital will determine the dividend policy of the company's value. The value of the company reflects the present value of the expected income in the future. The financial management function can maximize the value of the company. Optimal capital structure will also affect dividend policy and high dividend payout will be responded by investors as a sign that the company is in good condition. A high dividend policy will also be responded to by an increase in share prices which will increase the value company.